Inclusive and Disabled Friendly Pedestrian Path Strategy - Nahdatunnisa, Nahdatunnisa; Tahir, M. Arzal; Syah, Andi Al-Mustagfir; Setiadi , Ahsan Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pedestrian paths are an important aspect for a sustainable city, designed and equipped with supporting infrastructure that will be used by all levels of society. Revitalization of pedestrian paths must prioritize inclusivity and expand its benefits to all levels of society, including people with disabilities. This research aims to analyze the performance of pedestrian paths in urban public green open space areas, by carrying out a simulation process on the available ramps. The method used in this research is the data triangulation method. The results obtained are a model, an optimal pedestrian path development strategy and detailed ramp sizes that can be accessed by people with disabilities with a path slope of 7°, a path height of 25 cm from the road surface, with a minimum width of 150 cm and a slope/slope length of 175 cm.